Pinning down the value of statistical life - Thomas J. Kniesner; William Kip Viscusi; Christopher Woock; James Patrick Ziliak (Institute for the Study of Labor (IZA), 2007)
Our research addresses fundamental long-standing concerns in the compensating wage differentials literature and its public policy implications: the econometric properties of estimates of the value of statistical life (VSL) and the wide range of such estimates from about 0.5 million to about 21 million. We address most of the prominent econometric issues by applying panel data, a new and more accurate fatality risk measure, and systematic selection of panel estimator in our research. Controlling for measurement error, endogeneity, individual heterogeneity, and state dependence yields both a reasonable average level and narrow range for the estimated value of a statistical life of about 5.57.5 million.
Keywords: 330; VSL; panel data; fixed effects; random effects; PSID; Wert des Lebens; Menschen; Bewertung; Panel; Schätztheorie; Verdienstausfall; Schätzung; Theorie; USA